The Reality of Mut'ah Marriage in Indonesia: Reinterpretation of the Opinion of Shia Scholars - Sulihkhodin, Moh. Alfin; Asadurrohman, Muhammad; Wibowo, Aris (Research and Development Institution, Darussalam Institute for Islamic Studies, 2022)
The purpose of this research is to describe the reality of mut’ah marriage in Indonesia by making an attempt to interpret the views of Shi’ah scholars. The discourse related to mut’ah marriage isn’t longer considered a new discuss in Indonesia. There have been several previous studies related to this problem. Starting from research that focuses on the discuss related to the legal controversy of contract marriage, efforts to compare Islamic law with positive law in Indonesia, attempts to criticize the hadith relating to the ability to implement mut’ah marriage, and research that is directly involved in the field. Basically, this opinion about the permissibility of marriage was specifically conveyed by the Shi’ah scholars. And the Sunnis generally forbiden it. This study used a qualitative approach with the library study method. The writer chose the research using the literature study method to make it easier to collect data related to the reality of the practice of mut'ah marriage in Indonesia. The research results show that: The practice of mut’ah marriage in Iran is actually regulated in a certain regulation. But, in Indonesia the marriage that are listed and protected in the regulations are marriages that are permanent (daim).